The Relevance of Edutainment Principles in Early Children's Education - Windisyah Putra (Journal of Educational Analytics, 2023)
This research is expected to provide information and describe how the relevance of the application of edutainment principles in early childhood education. This research is qualitative research, using an analytical descriptive approach. The results of the study show; (1) the relevance of the edutainment principle actualized in the daily activity plan, including; initial activities (special institutional activities and Islamic religious education, core activities, rest and eating and closing activities; (2) the creation of positive and fun learning between teachers and students in interacting; (3) the existence of motivation and ways of learning that appreciate the learning style and modalities of students so that good learning outcomes are achieved; (4) classical activities emphasize habituation and training to increase self-reliance, courage, discipline and responsibility for him; (5) core activities are carried out through a process of exploration, experimentation, elaboration, and confirmation aimed at activating the child's attention, abilities and emotional social; and (6) the final activity is calming the child and is classically given.